(untitled) (Conferencea, 2023)
The most important thing in development of the optimal technological process is to justify the purpose and evaluate the effectiveness of technological operations or its individual elements. Various methods and criteria were analyzed in the article, which, from the point of view of matching optimal solutions at different levels, it is preferable to develop processes from the most general issues to their detail.